Ответ:
будет вот так
Объяснение:
100% правильно
Ответы:
5. 1)
2)
6.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
будет вот так
Объяснение:
100% правильно
Ответы:
5. 1)
![\frac{4^6*2^9}{32^4} = \frac{(2^2)^6*2^9}{(2^5)^4} = \frac{2^{12}*2^9}{2^{20} } = \frac{2^{21}}{2^{20}} = 2 \frac{4^6*2^9}{32^4} = \frac{(2^2)^6*2^9}{(2^5)^4} = \frac{2^{12}*2^9}{2^{20} } = \frac{2^{21}}{2^{20}} = 2](https://tex.z-dn.net/?f=%5Cfrac%7B4%5E6%2A2%5E9%7D%7B32%5E4%7D%20%3D%20%5Cfrac%7B%282%5E2%29%5E6%2A2%5E9%7D%7B%282%5E5%29%5E4%7D%20%3D%20%5Cfrac%7B2%5E%7B12%7D%2A2%5E9%7D%7B2%5E%7B20%7D%20%7D%20%20%3D%20%5Cfrac%7B2%5E%7B21%7D%7D%7B2%5E%7B20%7D%7D%20%3D%202)
2)
![(\frac{3}{8})^{-5}*(\frac{3}{8})^6 = \frac{3}{8}=0,375 (\frac{3}{8})^{-5}*(\frac{3}{8})^6 = \frac{3}{8}=0,375](https://tex.z-dn.net/?f=%28%5Cfrac%7B3%7D%7B8%7D%29%5E%7B-5%7D%2A%28%5Cfrac%7B3%7D%7B8%7D%29%5E6%20%3D%20%5Cfrac%7B3%7D%7B8%7D%3D0%2C375)
6.![125a^6b^3*(-0,2a^2b^4)^3 = 125a^6b^3*(-0,008a^6b^{12})= -a^{12}b^{15} 125a^6b^3*(-0,2a^2b^4)^3 = 125a^6b^3*(-0,008a^6b^{12})= -a^{12}b^{15}](https://tex.z-dn.net/?f=125a%5E6b%5E3%2A%28-0%2C2a%5E2b%5E4%29%5E3%20%3D%20125a%5E6b%5E3%2A%28-0%2C008a%5E6b%5E%7B12%7D%29%3D%20-a%5E%7B12%7Db%5E%7B15%7D)